A small engineered protein lacks structural uniqueness by increasing the side-chain conformational entropy - Furukawa, Koji (The National Academy of Sciences of the USA, 1996)
A small globular protein, the third repeat of the c-Myb DNA-binding domain, which is composed of 54 amino acid residues, was engineered so as to understand the structural uniqueness of native proteins. This small protein has three α-helices that form a helix-turn-helix structure, which is maintained by the hydrophobic core with three Ile residues. One of the mutant proteins, with two of the buried Ile (Ile-155 and Ile-181) substituted with Leu residues, showed multiple conformations, as monitored by heteronuclear magnetic resonance spectroscopy for (13)C- and (15)N-labeled proteins. The increase in the side-chain conformational entropy, caused by changing the Ile to a Leu residue on an α-helix, could engender the lack of structural uniqueness. In native proteins, the conformations of not only the β-branched side chains, but also those of the neighboring bulky side chains, can be greatly restricted, depending upon the local backbone structure.